Méthode de piano forté du Conservatoire vol. 1 - Adam, Louis 1758-1848 (Bonn Cologne Simrock, 1815)
Louis Adam (1758-1848) was a French composer, music teacher, and piano virtuoso. He spent over four decades, from 1797 through 1842, as Professor of Pianoforte at the Conservatoire de Paris, whrere he taught Friedrich Kalkbrenner and Ferdinand Hérold, among others. In addition to being a skilled pianist, he composed a number of piano pieces that were in vogue at the time, especially some variations on 'Le Bon Roi Dagobert'. He also wrote two standard instruction books for piano: Méthode ou principe générale du doigté pour le forté-piano (1798) and Méthode nouvelle pour le piano (1802). His influential 'Méthode de piano du Conservatoire', which contributed to the advancement of piano technique in Paris, was first published in 1804
First volume of three, for the complete version see 07D42
Originally published in 1804
choix de morceaux doigtés dans les différens caractères et mouvemens
Keywords: Conservatoire de Paris (France); 19th Century (1801-1900); Music education; Method; Piano; Paris (France); arpeggio; artikulatie; Bach, J.S.; catalogus Simrock; dubbelslag; pianoforte; polyritmiek; gesticuleren; tremblement lié; tremolo; trillervingerzetting; handhouding; vingerzetting; klavecimbel; kleine versieringsnootjes op de slag; lengte van port de voix; Silbermann, G; bovensecunde triller in 19e eeuw; duim op boventoets; hoofdnoottriller; mordent - hoofdnoottriller; tertsvingerzetting; triolen vs achtstes aanpassen; Vahal, J; vingerwisseling bij toonherhaling